2011
DOI: 10.1007/s00213-011-2277-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of ketamine and phencyclidine with other antagonists of the NMDA receptor in rodent assays of attention and working memory

Abstract: Overall, the opportunity to induce a selective cognitive deficit in attention (5CSRT) or working memory (DMTP) in the rat is limited by both the NMDAR antagonist and the dose range used. The importance of a preclinical focus on ketamine, which is used more frequently in clinical settings, is limited by the extent to which cognitive effects can be both detected and quantified using this exposure regimen within these two operant assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
61
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 47 publications
14
61
0
Order By: Relevance
“…In contrast, the effects of NR2B NAMs have been less well studied and have produced mixed results. Unlike NMDA channel blockers such as MK-801 or phencyclidine systemic administration of NR2B NAMs in rats does not adversely affect spatial memory in operant-delayed match to position tasks (Higgins et al, 2003;Smith et al, 2011). Similar results were also seen in the Morris watermaze task where systemic NR2B NAM treatment had no effect on memory acquisition or retention for the location of the hidden platform (Guscott et al, 2003;Higgins et al, 2005;Higgins et al, 2003;Okiyama et al, 1997).…”
Section: Introductionmentioning
confidence: 57%
“…In contrast, the effects of NR2B NAMs have been less well studied and have produced mixed results. Unlike NMDA channel blockers such as MK-801 or phencyclidine systemic administration of NR2B NAMs in rats does not adversely affect spatial memory in operant-delayed match to position tasks (Higgins et al, 2003;Smith et al, 2011). Similar results were also seen in the Morris watermaze task where systemic NR2B NAM treatment had no effect on memory acquisition or retention for the location of the hidden platform (Guscott et al, 2003;Higgins et al, 2005;Higgins et al, 2003;Okiyama et al, 1997).…”
Section: Introductionmentioning
confidence: 57%
“…In these previous studies, CP-101,606 was effective at reducing haloperidol-induced catalepsy and neuropathic pain in rats over the dose range (2-20 mg/kg) used in the present study. Furthermore, comparative effects of ketamine and CP-101,606 over the dose ranges used in this study in a number of different behavioral paradigms have also been reported (Dix et al, 2010;Gilmour et al, 2012;Smith et al, 2011).…”
Section: Drug Treatmentmentioning
confidence: 64%
“…As a general note, systemic MK-801 and ketamine are typically associated with acute motoric effects (Gilmour et al, 2009;Smith et al, 2011). Indeed, such effects were often observed in the first 10-15 min following injections during the sub-chronic administration period.…”
Section: Resultsmentioning
confidence: 99%